Co-creation for sustainability : the UN SDGs and the power of local partnerships - Ansell, Christopher K., 1957-; Sørensen, Eva, 1957-; Torfing, Jacob (Emerald Publishing Limited, 2022)
The ebook edition of this title is Open Access and freely available to read online. The UN's Sustainable Development Goals (SDGs) set an ambitious agenda for global problem-solving and create a framework to achieve it through the power of partnerships. Goal 17 points to the central importance of partnerships, networks, and multi-stakeholder collaborations for bringing together a broad range of actors to accomplish the first 16 goals. Only through such partnerships can the distributed knowledge, resources and capacity of government agencies, private enterprises, political activists, local communities, and international NGOs be effectively combined to produce the major breakthroughs in sustainability that the SDGs envision. Co-Creation for Sustainability sets out a strategy of partnership, with an emphasis on how global goals can be translated into local action. Co-creation brings multiple parties together--including citizens--to collaboratively engage in innovative problem-solving. The book explains this strategy and describes how to foster the conditions necessary for its success. It details how leaders can spur co-creation and manage and overcome its practical challenges. Written to inspire public and private changemakers to find fundamental solutions to the pressing challenges that confront our social and natural environment, Co-creation for Sustainability: The UN SDGs and the Power of Partnerships provides intellectual resources and practical advice relevant for those who aspire to harness the talents, energy and perspectives of different sectors to build the momentum we need to realize a sustainable future.